HIV-1 Genomes Are Enriched in Memory CD4 + T-Cells with Short Half-Lives - Vincent Morcilla (American Society for Microbiology, 2021)

(untitled)
The design of future HIV-1 curative therapies requires a more thorough understanding of the distribution of genetically intact HIV-1 within T-cell subsets as well as the cellular mechanisms that maintain this reservoir. These genetically intact and presumably replication-competent proviruses make up the latent HIV-1 reservoir.